2016
DOI: 10.2989/16085906.2016.1189442
|View full text |Cite
|
Sign up to set email alerts
|

Choice in HIV testing: the acceptability and anticipated use of a self-administered at-home oral HIV test among South Africans

Abstract: Combination HIV prevention is being widely promoted by funders. This strategy aims to offer HIV prevention choices that can be selected and combined to decrease HIV risk in ways that fit with each individual's situation. Treatment as prevention and pre-exposure prophylaxis are two new evidence-based strategies to decrease HIV incidence, both of which require high HIV testing rates to be effective, and the Joint United Nations Programme on HIV/AIDS (UNAIDS) has set a goal of 90% of HIV-positive individuals know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 30 publications
8
41
1
Order By: Relevance
“…Interview data provided rationale for why STI clinic patients might be willing to deliver HIVST kits to their partners with PDPT, which could help facilitate disruption of STI and HIV transmission if implemented with favorable uptake. This data supports a growing body of evidence supporting the acceptability of HIVST (Ahmed-Little et al, 2016; Bavinton et al, 2013; Bustamante et al, 2017; Choko et al, 2015; Gaydos et al, 2011; Kelvin et al, 2016; Kurth et al, 2016; Lee, Brooks, Bolan, & Flynn, 2013; Pal et al, 2016; Prestage et al, 2016; Witzel, Rodger, Burns, Rhodes, & Weatherburn, 2016). Moreover, this research adds to prior data on the acceptability of secondary distribution of HIVST kits to sexual partners (Kalibala et al, 2014; Lippman et al, 2016; Masters et al, 2016; Prestage et al, 2016; Thirumurthy et al, 2016), indicating rationale for why individuals might find it acceptable.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Interview data provided rationale for why STI clinic patients might be willing to deliver HIVST kits to their partners with PDPT, which could help facilitate disruption of STI and HIV transmission if implemented with favorable uptake. This data supports a growing body of evidence supporting the acceptability of HIVST (Ahmed-Little et al, 2016; Bavinton et al, 2013; Bustamante et al, 2017; Choko et al, 2015; Gaydos et al, 2011; Kelvin et al, 2016; Kurth et al, 2016; Lee, Brooks, Bolan, & Flynn, 2013; Pal et al, 2016; Prestage et al, 2016; Witzel, Rodger, Burns, Rhodes, & Weatherburn, 2016). Moreover, this research adds to prior data on the acceptability of secondary distribution of HIVST kits to sexual partners (Kalibala et al, 2014; Lippman et al, 2016; Masters et al, 2016; Prestage et al, 2016; Thirumurthy et al, 2016), indicating rationale for why individuals might find it acceptable.…”
Section: Discussionsupporting
confidence: 82%
“…STI clinic stigma is further exacerbated with worries about social network members seeing them at the clinic (Lippman et al, 2016), necessitating the need for PDPT and secondary distribution of HIVST kits to reach some at-risk populations. Providing HIVST kits with PDPT was described as a convenient mechanism to overcome this barrier, consistent with prior findings about the convenience associated with HIVST (Ahmed-Little et al, 2016; Bavinton et al, 2013; Kelvin et al, 2016; Lippman et al, 2016; Witzel et al, 2016). …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is also consistent with the in-depth interviews, which found that participants who did not test at baseline or over follow-up had strong -but varied -preferences regarding the biological specimen used for the HIV test (oral fluid or blood). This variation in preference for blood versus oral HIV tests was also found in a qualitative study looking at views on oral self-testing among a sample of South African clinic attendees (Kelvin et al 2016). …”
Section: Implications Of Study Resultssupporting
confidence: 57%